Analysis of Mechanical Properties of Zn-0.5Fe-0.5Ag Alloy for Body Absorbed Implant Applications - Ramadhan, Arya Famas; Arafat, Andril; Habibie, Farhan; Nurdin, Hendri; Mulianti, Mulianti (invotek, 2024)
Implants that can be absorbed by the body may be developed using alloy materials based on zinc (Zn), iron (Fe), copper (Cu), and silver (Ag). Zn-based alloys are known for their faster biodegradation rates, making them particularly suitable for biodegradable implant applications. The aim of this study is to determine the corrosion rate and hardness of Zn-0.5Fe-0.5Ag alloy specimens, as well as to examine the effects of heat treatment and the addition of Fe and Ag elements. The research utilizes a direct experimental observation method to analyze the mechanical properties of the Zn-0.5Fe-0.5Ag alloy. The microstructural analysis reveals differences between pure Zn specimens and Zn-0.5Fe-0.5Ag alloy specimens. In pure Zn, the largest grain size is observed in specimens without annealing treatment, while the smallest grain size is found in specimens annealed at 350°C. For the Zn-0.5Fe-0.5Ag alloy, the smallest grain size is observed in specimens annealed at 400°C, while the largest grain size appears in those annealed at 350°C. The addition of Fe and Ag to pure Zn significantly increases the hardness, with the hardness value rising from 33.77 HV (pure Zn) to 61.64 HV. In terms of corrosion, the highest corrosion rate in pure Zn was found in specimens without annealing. In contrast, the highest corrosion rate in the Zn-0.5Fe-0.5Ag alloy was observed in specimens annealed at 400°C. In conclusion, the addition of Fe and Ag elements, along with heat treatment, significantly affects the mechanical properties of the Zn-0.5Fe-0.5Ag alloy, improving both its hardness and influencing its corrosion behavior.